Optimum currency area theory: A selective review - Julius Horvath (Bank of Finland, Institute for Economies in Transition (BOFIT), 2003)
The first part of this paper is a review of significant papers in the vast literature on optimum currency area (OCA) theory.The author focuses on the main classical contributions, then considers modern treatment of OCA theory.The second part considers empirical literature on the types of geographical areas that might constitute optimum currency areas, particularly with respect to asymmetry and symmetry of shocks.
URN:NBN:fi:bof-201408072144
Keywords: E42; F33; 330